Relationship between inflammation and the severity of Recurrent Respiratory Papillomatosis - El Achkar, Vivian Narana Ribeiro [UNESP]; Duarte, Andressa; Carlos, Román; León, Jorge Esquiche; Ribeiro-Silva, Alfredo; Pignatari, Shirley Shizue Nagata; Kaminagakura, Estela [UNESP] (Elsevier, 2020)
Objective: To characterize inflammatory cells in Recurrent Respiratory Papillomatosis (RRP) and to correlate it with severity using the Derkay laryngoscopic scale. Materials and methods: The data and biopsies from 36 patients with Juvenile (JRRP) and 56 patients with Adult (ARRP) were collected and analyzed under light microscopy. The patients were separated into groups according to the Derkay index: ≥20 for the most severe and < 20 for the less severe cases. Immunohistochemical analysis using CD3, CD4, CD8, CD15, CD20, CD68, FoxP3 and MUM-1 antibodies was performed, and the inflammatory cells were quantified. All the clinicopathological characteristics and the results of the immunohistochemical analysis were compared among the groups proposed using the Chi-Square test and correlated through the Spearman correlation test. Results: The ARRP showed significantly higher quantities of CD3+, CD8+ and MUM1+ cells (p < .05) than the JRRP samples. The presence of CD15+ cells showed positive correlation with the Derkay index (p < .05), while the MUM-1+ cells showed an inverse correlation (p = .01). Conclusion: There are differences between the inflammatory cells population in the juvenile and adult groups and it can be related to disease severity.
Keywords: Human papillomavirus; Inflammatory cells; Laryngeal papillomatosis; Squamous cell papillomatosis